THE EUROPEAN REGULATORY FRAMEWORK FOR FARM ADVISORY SERVICES - Jovanić, Tatjana; Tanja Đelić, Anastazija (Economics of Agriculture, 2013)
In the European Union farm advisory systems preliminary purpose is to help farmers to better understand and meet the requirements of the EU rules on environmental aspects of agriculture. A great shift towards these goals and the importance of the farm advisory systems took place in 2003, when the reform of the Common Agricultural Policy introduced the cross compliance mechanism, which is in force as of 2005, and links direct payments directly to farmers compliance with basic standards related to the environment, food safety, animal and plant health and welfare, and in general, the requirement to maintain land in good agricultural and environmental conditions. The purpose of this paper is to define the regulatory framework of farm advisory system and services in the EU and raise the question of the lack of interest and appropriate mechanisms to broaden the activities of Serbian Agricultural Extension Services towards control of cross compliance requirements and good agricultural practices.